Mediasi sengketa perbankan syariah dalam prespektif fiqh muamalah dan hukum positif - noviyanti, widiyarani (Maliki Interdisciplinary Journal, 2026)
Mediation in Islamic banking disputes faces a major challenge: Islamic jurisprudence (fiqh muamalah) emphasizes peaceful resolution through deliberation and substantive justice, while Indonesian positive law tends to prioritize litigation in religious or Islamic commercial courts. This study analyzes how to integrate these two approaches to strengthen mediation as the primary dispute resolution method. Applying normative and comparative legal methods, the study examines Islamic values ​​such as sulh alongside Indonesian regulations regarding arbitration and other dispute resolution methods. The results indicate that integrating the principle of islah from Islamic law with Law No. 30 of 1999 can substantially improve the effectiveness of the mediation process, with a success rate of up to 80%. In conclusion, harmonizing Islamic jurisprudence and national law can improve the Islamic justice system by prioritizing mediation as a fairer and more efficient solution.